Pattern of inculcating multicultural values in students at State Senior High School 1 Kendal - Fauzi, Malik Ridwan; Pudji Astuti, Tri Marhaeni; Atmadja, Hamdan Tri (JESS (Journal of Educational Social Studies), 2022)
The aims of this study was to analyze the role of schools in inculcating multicultural values, the driving and inhibiting factors for inculcating multicultural values, and the pattern of inculcating multicultural values in State Senior High School 1 Kendal. This research used a qualitative approach to the type of phenomenology. Data collection techniques are interviews, observations, and documentation studies. The results show that schools have a socialization role, providing knowledge about multicultural values; the role of education is to educate and provide an example of multicultural behavior; and the role of evaluation is to provide corrections for violations of multicultural values in schools. The driving factor for the cultivation of multicultural value is an open student family environment, teachers' knowledge of multicultural values, high school curriculum policies that accommodate student differences, as well as school programs that support the cultivation of values. The inhibiting factors are harsh environmental factors, and problematic student family environmental factors and uneven teacher knowledge related to the concept of multicultural education. The pattern of cultivating multicultural values at State Senior High School 1 Kendal is a contribution and additive pattern, by introducing multicultural values in learning indirectly by introducing heroes or figures who come from different cultural, religious and regional backgrounds. In addition, by adapting multicultural values into the material in the subject.